PEMBELAJARAN MENULIS TEKS BERITA DENGAN METODE PROJECT BASED LEARNING BERBANTU MEDIA PADLET BAGI SISWA KELAS VII - Ashadi, Salsabilah Syifaun Putri; Saleh, Nurul Intan; Haliq, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the news writing skills of seventh grade students through Project Based Learning (PjBL) with Padlet media. PjBL focuses on student activities to produce real products, while Padlet supports collaboration, idea sharing, and feedback. This study found that the use of PjBL and Padlet effectively increased students' motivation, creativity, critical thinking, collaboration skills, and understanding of the structure and elements of news texts. This approach is an innovative alternative to develop writing skills and provide meaningful learning experiences.